Epidemiology, Injury Patterns, and Treatment of Meniscal Tears in Pediatric Patients: A 16-Year Experience of a Single Center. Issue 12 (18th December 2019) - Jackson, Taylor; Fabricant, Peter D.; Beck, Nicholas; Storey, Eileen; Patel, Neeraj M.; Ganley, Theodore J.
Background: Meniscal injuries in children continue to increase, which may be attributable to increasing levels of athletic participation and may be associated with additional injuries or need for additional surgeries. Purpose: To better understand the patterns of pediatric meniscal injuries by analyzing tear location, morphologic features, and associated injury patterns over a 16-year period. Study Design: Case series; Level of evidence, 4. Methods: Pediatric patients were identified and were included in the study if age at the time of initial surgery for meniscal tear was between 5 and 14 years for female patients and 5 and 16 years for male patients. Patients were observed until age 18, and any subsequent surgeries were noted. Demographic factors, tear type and location, associated injuries, and treatment type were analyzed. Results: Mean patient age at surgery was 13.3 years, and 37% of patients were female. A total of 1040 arthroscopic meniscal surgeries in 880 pediatric patients were evaluated. There were 160 reoperations in 138 patients, representing a reoperation rate of 15%. These included 98 reoperations on the ipsilateral knee in 88 patients and 62 operations for injuries to the contralateral knee in 50 patients; 53% of surgeries were meniscal repair, as opposed to partial meniscectomy, and the most common technique was an all-inside repair (91%). Significant differences were identified between male and female patients. Male patients were more likely to have lateral meniscus (74% vs 65%), posterior horn (71% vs 60%), peripheral (45% vs 30%), and vertical tears (31% vs 21%); concomitant ACL injury (50% vs 40%); and an associated osteochondritis dissecans lesion (7% vs 4%). Female patients were more likely to have medial meniscus (24% vs 17%), anterior horn (25% vs 15%), and degenerative tears (34% vs 26%); discoid meniscus (33% vs 24%); and isolated meniscal tears (47% vs 33%). Conclusion: This evaluation of a large series of patients has helped characterize injury patterns associated with pediatric meniscal surgeries. Most meniscal tears were repaired (53%) and were associated with additional injuries (62%), especially anterior cruciate ligament injuries (48%). More than 25% of patients had a discoid meniscus. Injury patterns differed significantly between male and female patients.